META ANALISIS MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN KETERAMPILAN ABAD 21 - Karomatunnisa, Az-Zahra Aulia; Sholih, Jamilla Agustin Ummu; Hanifah, Nida; Prihantini, Prihantini (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to determine the effectiveness of the project based learning model in improving 21st century skills. The research method uses a qualitative approach based on the literature. Sources obtained from various kinds of reading materials such as books, articles, journals, and other literature. The sources used are relevant to the discussion. The project-based learning model is one of the project-based models, where students are more active in the learning process. Students will be given a project in the group learning process. 21st century skills are skills that must be possessed in the era of the industrial revolution 4.0 which requires its generations to become quality, creative, innovative, and critical human resources. This project-based learning is one way to face and prepare generations in the 21st century. This model will later be able to form skills that are in accordance with the era of the industrial revolution 4.0. Project-based learning is also equipped with a scientific approach. Along with the times and more and more learning models, one of which is a project-based learning model that can be applied by teachers as an effort to prepare the 21st century generation.